Carnap's Logical Syntax of Language - Wagner, P. author. aut Link
XIII, 270 p.
Keywords: This volume's aim is to provide an introduction to Carnap's book from a historical and philosophical perspective, each chapter focusing on one specific issue. The book will be of interest not only to Carnap scholars but to all those interested in the history of analytical philosophy.